PENGARUH KOMPETENSI SUMBERDAYA MANUSIA TERHADAP KINERJA PENYELENGGARA PENGAWASAN KETENAGAKERJAAN DI BALAI PENGAWASAN DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI UTARA - Anthonius Parlindungan Hutagalung; Joyce ., Rares; Fanley ., Pangemanan (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine whether attitudes, knowledge and motivation as competencies have an influence on the performance of State Civil Servants in the environment, in this case the labor inspection organizers at the Supervision Office of the Department of Manpower and Transmigration, North Sulawesi Province. This research uses quantitative methods with a descriptive approach carried out at the Supervisory Office of the Department of Manpower and Transmigration of North Sulawesi Province with a sample size of 50 respondents with a questionnaire instrument using a Likert scale analyzed by F test, t test and multiple regression.Â  The results showed that the residual values were normally distributed. Where the attitude variable affects the performance of the labor inspectorate, as well as the knowledge variable and the motivation variable which also have an effect.